Incidence of consumption and the price of fish in the malnutrition chronic - Cruz Castillo, Nelson (2020)
General objective of this research work was to determine the incidence of consumption and the price of fish in children with chronic malnutrition in the city of Huaraz – Ancash region. Year - 2017. Having contrasted the general hypothesis is corroborating that these variables affect in a significant way in children with chronic malnutrition, there is a highly significant relationship between the variables. Likewise, in contrast to the specific hypothesis, it was established that there is an important incidence of fish consumption. And that the price of fish has a highly significant relationship. The method of obtaining the information was carried out with the processing of the surveys to the mothers of the popular canteens, therefore, the statistical program conventional was used, which allowed the univariate analysis of the information. The study was complemented by the use of Microsoft's Word and Excel. We performed the analysis of statistical frequencies and their contrast of the hypothesis with the method of Chi-square and coefficient of contingency. What prevails in this study is the economic and social approach. JEL: I15